Novel thidiazuron-derived inhibitors of cytokinin oxidase/dehydrogenase - Nisler, Jaroslav; Kopečný, David; Končitíková, Radka; Zatloukal, Marek; Bazgier, Václav; Berka, Karel; Zalabák, David; Briozzo, Pierre; Strnad, Miroslav; Spíchal, Lukáš (Plant molecular biology, 2016)
Two new TDZ derivatives (HETDZ and 3FMTDZ) are very potent inhibitors of CKX and are promising candidates for in vivo studies. Cytokinin hormones regulate a wide range of essential processes in plants. Thidiazuron (N-phenyl-N'-1,2,3-thiadiazol-5-yl urea, TDZ), formerly registered as a cotton defoliant, is a well known inhibitor of cytokinin oxidase/dehydrogenase (CKX), an enzyme catalyzing the degradation of cytokinins. TDZ thus increases the lifetime of cytokinins and their effects in plants. We used in silico modeling to design, synthesize and characterize twenty new TDZ derivatives with improved inhibitory properties. Two compounds, namely 1-[1,2,3]thiadiazol-5-yl-3-(3-trifluoromethoxy-phenyl)urea (3FMTDZ) and 1-[2-(2-hydroxyethyl)phenyl]-3-(1,2,3-thiadiazol-5-yl)urea (HETDZ), displayed up to 15-fold lower IC 50 values compared with TDZ for AtCKX2 from Arabidopsis thaliana and ZmCKX1 and ZmCKX4a from Zea mays. Binding modes of 3FMTDZ and HETDZ were analyzed by X-ray crystallography. Crystal structure complexes, solved at 2.0 Å resolution, revealed that HETDZ and 3FMTDZ bound differently in the active site of ZmCKX4a: the thiadiazolyl ring of 3FMTDZ was positioned over the isoalloxazine ring of FAD, whereas that of HETDZ had the opposite orientation, pointing toward the entrance of the active site. The compounds were further tested for cytokinin activity in several cytokinin bioassays. We suggest that the combination of simple synthesis, lowered cytokinin activity, and enhanced inhibitory effects on CKX isoforms, makes 3FMTDZ and HETDZ suitable candidates for in vivo studies.
Keywords: Organic synthesis; fenylmočovinové sloučeniny; Crystal structure; Cytokinin; cytokininy; thiadiazoly; Thiadiazoles; Cytokinin oxidase/dehydrogenase; Thidiazuron; Enzyme Inhibitors; Oxidoreductases; Molecular docking; inhibitory enzymů; oxidoreduktasy; Phenylurea Compounds; Cytokinins